An Effect of Product Quality, Price, and Word of Mouth on Buying Interest : A case of Tretes Porridge in Binjai - Selfira Yap; M Umar Maya Putra; Syafrida Damanik (Institute of Computer Science (IOCS), 2022)
Small and medium enterprises (SMEs) is one of the supporting economic growths of a region. Small and medium size business can be developed by increasing the buying interest of the people around. Buying interest is the desire that arises from consumers to a product as a result of the consumer's observation of a product. This research is quantitative research with a sample of 109 respondents. This study focuses on the effect of product quality, price, and word of mouth on interest buying : a case of Bubur Tretes Binjai. This research was conducted in Binjai . The population of this study is the customer of Bubur Tretes that is located in Binjai. The researcher concluded that taking a sample of 109 respondents. Primary data were gathered by using questionnaires. The data were analyzed by using structural equation modeling-partial least squares (SEM-PLS) with SmartPLS software. The result of this study indicated that the variable product quality (X1) partially had a significant effect on buying interest, the price variable (X2) partially had not significant effect on buying interest, and word of mouth variable (X3) partially had a significant effect on buying interest. Simultaneously, product quality, price , and word of mouth influence buying interest on the traditional product of Bubur Tretes in Binjai. From the results of data processing, it was found that the coefficient of determination was 69.2% which indicates that X1, X2, and X3 together were able to influence Y by 69.2% with a moderate category, the remaining 30.8% was influenced by other factors.